Study on the influence of various broodstock diets on etroplus suratensis (bloch 1790) - Jyoti Ganesh Gabhane (KUFOS, 2019)
Abstract-The study was carried out to understand the influence of various diets on the broodstock development and breeding of pearlspot, Etroplus suratensis reared under freshwater environment. Fishes were sourced from low saline farm and were acclimatised to freshwater condition in the hatchery. Four diets with varying protein and lipid levels ranging from 36% to 44% and 7.6 to 11% were used. The fishes were fed ad libitum twice daily and once a week feed holiday was observed. The feeds used were T1 (36% CP and 7.6 % CF), T2 (40% CP and 8% CF), T3 (44% CP and 11% CL) and T4 (Clam meat and Shrimp meat). The water quality parameters were checked daily with the temperature ranging from 25.0-28.0⁰C, pH 7.7-8.5, Ammonia 0-0.009 ppm, DO 6-8 mg/l, Nitrite0-0.1 ppm and Nitrate 0-10 ppm. The study revealed that the biochemical composition of the pearlspot adult fish expressed in wet matter basis composed protein 16.59 %, fat 2.42 %, and NFE 1.41%. The average GSI % of the fish in the month of October was observed around 1.94±0.02. It has been reported that the pearlspot brooders when provided diet with 40% CP and 8 % CF, gave multiple spawning with an average eggs 958±52 and 98% fertilization in indoor environment while the same feed when applied to the outdoor tank it induced 12 pair formation and obtained 8 spawning with an average of 579.75±92.4 eggs. This confirms the potential of this feed to induce spawning in natural outdoor pond system and can be immensely useful for aqua farmers.